IMPROVING ACCOUNTING FOR LONG-TERM ASSETS IN ACCORDANCE WITH INTERNATIONAL STANDARDS (World Economics and Finance Bulletin, 2024)
In this article, the approaches of foreign and domestic scientists to the accounting of long-term assets based on international standards, as well as the principles of recognition, evaluation and accounting of long-term assets in international standards were studied. According to the fundamental and qualitative description of long-term assets, it is appropriate to categorize them on the basis of reliability, relevance, truthful presentation, i.e. completeness, neutrality, error-free, comparability, verifiability, timeliness, comprehensibility. The basic principles of accounting define the conceptual framework for accounting for long-term assets.
Keywords: Long-term assets; method of calculation; continuity of activity; continuity of the ratio between income and expenses